CBR Performance of Geosynthetic-Reinforced Subgrades in Layered and Homogeneous Soil Systems - Nur Rasfina, Mahyan; Mastura, Azmi; Fauziah, Ahmad; Siti Noor Linda, Taib (Springer Nature, 2026)
This study systematically evaluates the effectiveness of geosynthetic reinforcement on subgrade soils prevalent in tropical climates, specifically those involving sandy, lateritic, and layered sand-over-laterite soils, through comprehensive laboratory. California bearing ratio (CBR) tests conducted under both soaked and unsoaked conditions. Reinforcements using woven geotextile and biaxial geogrid were installed at varying depths (0.3H, 0.4H, and 0.5H), enabling a detailed analysis of the placement effects on soil strength. Results indicate that the geotextile consistently outperformed the geogrid across all soil types, markedly enhancing the soaked bearing capacity, particularly in sandy soils (reinforcement ratio η 2.02 at 0.3H), due to its superior confinement and moisture resilience. In cohesive lateritic soils, deeper reinforcement placement (0.5H) provided maximum efficiency (η 1.52), effectively controlling plastic deformation from moisture exposure. For layered configurations, placing reinforcement at the sand–laterite interface notably improved stiffness transitions, maximizing absolute bearing capacity (CBR 13.84% at 0.5H). Optimum reinforcement efficiency, however, occurred at shallower depths (0.3H). A critical trade-off between maximum strength and reinforcement efficiency was identified, emphasizing depth-specific optimization strategies tailored to individual soil behaviours. These findings significantly advance practical pavement design guidelines, providing clear, empirically based recommendations for geosynthetic type and optimal placement depth, thereby supporting the development of sustainable and resilient pavement infrastructures that align with the Sustainable Development Goals (SDG 9, SDG 11).